2014
DOI: 10.15628/holos.2014.1378
|View full text |Cite
|
Sign up to set email alerts
|

Atributos Físicos E Ph De Um Fragmento Do Rio Taquari Sob a Mineração De Bauxita No Planalto De Poços De Caldas – Mg

Abstract: O presente trabalho objetivou avaliar a qualidade física de um curso d’água localizado no Planalto de Poços de Caldas (MG) antes, durante e após a mineração de bauxita. Para tanto, foram analisados alguns parâmetros físicos que refletem a qualidade d’água do Rio Taquari, em diferentes períodos do processo de mineração, as coletas duraram três meses em cada época: antes; durante; após, e dois anos depois da mineração; a primeira coleta foi em janeiro 2006 e a última em fevereiro de 2009. A coleta das amostras s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
3
0
2

Year Published

2017
2017
2023
2023

Publication Types

Select...
2
2

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 17 publications
0
3
0
2
Order By: Relevance
“…-LOCALIZAÇÃO E GEOLOGIA DO PLANALTO A microrregião engloba vários municípios mineiros e alguns paulistas, influenciada historicamente por rotas econômicas, posses de terras ou sesmaria e títulos de propriedades, principalmente após 1805. Situa-se numa caldeira vulcânica em uma região do domínio fitogeográfico da Mata Atlântica (BARROS, 2014).…”
Section: Resultados E Discussão -Contexto Históricounclassified
“…-LOCALIZAÇÃO E GEOLOGIA DO PLANALTO A microrregião engloba vários municípios mineiros e alguns paulistas, influenciada historicamente por rotas econômicas, posses de terras ou sesmaria e títulos de propriedades, principalmente após 1805. Situa-se numa caldeira vulcânica em uma região do domínio fitogeográfico da Mata Atlântica (BARROS, 2014).…”
Section: Resultados E Discussão -Contexto Históricounclassified
“…The minimum, maximum, mean and standard deviation of the chlorophyll-a and total phosphorus variables of 15 sampling stations in the rainy and dry season can be observed in Table 5. In the Water Quality Assessment Program, which comprised two campaigns, dry season and rainy season, CODEVASF (2014) attributes the phosphorus concentrations found in the water to the use of agrochemicals from agricultural areas, which can later be deposited at the bottom of rivers and lakes, which can be released into the water through biochemical processes. Besides this, other sources of phosphorus can be cited, such as the discharge of untreated household effluents from the irrigated perimeter housing plots.…”
Section: Application Of the Trophic State Index -Tsimentioning
confidence: 99%
“…This demonstrated that the anthropic activities performed in the Cotinguiba/Pindoba Perimeter, mainly agriculture and fish farming, contributed to the increase of the total phosphorus nutrient in the aquatic environment. CODEVASF (2014) reported on the significant presence of macrophytes in the perimeter water drainage.…”
Section: Application Of the Trophic State Index -Tsimentioning
confidence: 99%
“…Mountainous habitats translate into a wide diversity of ecosystem types, particularly specific forest types present at high altitudes, including forests, savannas, grasslands, rocky outcrop vegetation, and swamps (Scarano, Ceotto & Martinelli, 2016). The vegetation cover of Campos de Altitude (grassland mountainous vegetation) is predominantly formed by shrubs, herbs, and grasses in interspersed rocky outcrops, shallow soils, and occasional swamps (Ribeiro, Medina, & Scarano, 2007), and has been the vegetation with higher sensitivity to conversion of use (Pillar, Müller, Castilhos & Jacques, 2009;Barros, 2014) Among Brazilian plant physiognomies present in mountainous regions, subject to loss of vegetation cover, Campos de Altitude is present, in Brazil, in the Atlantic Forest, Amazon, Cerrado, and Pantanal (wetlands) biomes (Scarano, Ceotto, & Martinelli, 2016;Urbanetz et al, 2012;Zucco et al, 2011), in an altitudinal range from 1,200 m to 3,000 m. There are also 'Campos Rupestres' in higher altitudes within the Cerrado biome ranging from 1,000 to 2,000 m (Scarano, Ceotto & Martinelli, 2016;Fernandes et al 2014;Zucco et al, 2011).…”
Section: Introductionmentioning
confidence: 99%